2020
DOI: 10.1177/1076029620912020
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoprotein (a) on Postoperative Day 3: A Strong Predictor of Portal and/or Splenic Vein Thrombosis in Cirrhotic Patients With Splenectomy

Abstract: Elevated lipoprotein (a) [Lp(a)] is related to the incidence of lower limb deep vein thrombosis and pulmonary embolism. Its role in portal and/or splenic vein thrombosis (PSVT) is not established. A total of 77 consecutive patients who underwent splenectomy for cirrhotic portal hypertension were prospectively studied between 2014 and 2017. The impact of Lp(a) on preoperative day 1 and postoperative days (PODs) 1, 3, 5, 7, and 14 was analyzed. Color Doppler ultrasound examination was performed for the diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…The literature search identified 569 articles that were assessed for eligibility, and two studies include by searching the reference lists and reviewed articles. Finally, 18 studies 1,6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were included in the meta-analysis after removing duplicates, irrelevant papers, and articles did not meet inclusion criteria or various reasons, among which one study was excluded because it was low quality (NOS score < 6). (Fig.…”
Section: Results Study Selection and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search identified 569 articles that were assessed for eligibility, and two studies include by searching the reference lists and reviewed articles. Finally, 18 studies 1,6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were included in the meta-analysis after removing duplicates, irrelevant papers, and articles did not meet inclusion criteria or various reasons, among which one study was excluded because it was low quality (NOS score < 6). (Fig.…”
Section: Results Study Selection and Quality Assessmentmentioning
confidence: 99%
“…Fifteen studies 1,6,[12][13][14][15][16][17][18][20][21][22][24][25][26] reported the sex ratio of patients in the thrombotic versus non-thrombotic group. Meta-analysis indicated that sex was not significantly associated with PVST (OR 1.05, 95% CI 0.83-1.32, P = 0.680) (Fig.…”
Section: Sexmentioning
confidence: 99%
“…42 A prospective cohort study including 77 patients who underwent a splenectomy due to portal hypertension indicated that the lipoprotein(a) concentration postoperatively was a reliable predictor of portal and/or splenic vein thrombosis (PSVT). 43 Furthermore, patients with PSVT exhibited higher lipoprotein(a) levels compared to those without PSVT following operation.…”
Section: Portal Hypertensionmentioning
confidence: 99%
“…For instance, a prospective study of 77 Chinese patients showed that the Lp(a) concentration was abnormal in cirrhotic patients with portal and/or splenic vein thrombosis following splenectomy, indicating that monitoring serum Lp(a) levels could be a valuable tool to predict early portal and/or splenic vein thrombosis after splenectomy. [69] Moreover, high Lp(a) plasma level might be an independent risk factor for thrombotic events in Chinese patients with nonvalvular atrial fibrillation and a low CHA2DS2-VASc score. [70] Two prospective cohort studies in Chinese patients also suggested increased serum Lp(a) level as an independent predictor of deep vein thrombosis in patients with spinal cord injuries or acute ischemic stroke, suggesting a possible role of Lp(a) in the pathogenesis of deep vein thrombosis.…”
Section: Spectrum Of Lp(a)-related Disease In the Chinese Populationmentioning
confidence: 99%